Video Demonstration: Effects on Student’s Metacognitive Skills in Science - Nova Joy C. Barri; Dyn Carl D. Lorete; Krizzia Angielou L. Pacifico; Anamarie G. Valdez (ASEAN Journal of Science and Engineering Education, 2023)
The study investigated the effects of video demonstration on the metacognitive skills of students in science subjects. The 38 respondents are enumerated from Bachelor of Secondary Education major in Science students of Sultan Kudarat State Universit, the Philippines. This study utilized a quantitative research design to determine the variables of the study and the relationship that occurs between them. The results gathered were treated and analyzed using a t-test and mean rating. The results showed from the collected data, revealed that there is a significant difference in terms of thinking, understanding, performing, and reasoning than without the intervention of video demonstration as seen in the results of the two sets of tests given to the respondents. The teaching strategy using video demonstration is effective for the respondents in this study. Moreover, this strategy can be maximized by the teachers in delivering the lessons. As a result, it is recommended to educational institutions to enhance and strengthen their support in enhancing the skills in creating video demonstrations for their class discussions